2021
DOI: 10.1021/acsnano.1c00942
|View full text |Cite
|
Sign up to set email alerts
|

Precise Implantation of an Archimedean Ag@Cu12 Cuboctahedron into a Platonic Cu4Bis(diphenylphosphino)hexane6 Tetrahedron

Abstract: Precision loading of nanoclusters in confined spaces, which has been enthusiastically pursued in the scientific realm, is still associated with some mysteries of “how”, “when”, and “why”. Here, we isolated two similar heterometallic cluster-in-cage compounds, [Ag@Cu12S8@Cu4(dpph)6]­X (X = OH, SD/AgCu16a and X = PF6, SD/AgCu16b; SD = SunDi), by use of an antigalvanic reaction between organometallic [PhCCCu] n and Ph3CSH with elemental silver. Both compounds are formed by fitting an Archimedean Ag@Cu12 cubocta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 93 publications
1
31
0
Order By: Relevance
“…The results of ESI-MS revealed that the product of this alloy is a mixture nanocluster with different number of Cu atoms (10 ~21) doping. Similarly, the mixed doping of copper atom into silver nanolcuster was also reported for AgCu 16 nanocluster in the recent studies of Han et al [33] As shown in Figure S2, TGA reveals a weight loss of 42.96%, which is very close to the theoretical value (43.16%) for [Ag 45 Cu 17 S 12 (SC 4 H 9 ) 32 ](BPh 4 ) 4 . XPS measurements were carried out to reveal the element type and compared the binding energies of Ag in Ag 62À x Cu x and Ag 62 .…”
Section: Synthesis and Characterization Of Ag 62à X Cu Xsupporting
confidence: 83%
“…The results of ESI-MS revealed that the product of this alloy is a mixture nanocluster with different number of Cu atoms (10 ~21) doping. Similarly, the mixed doping of copper atom into silver nanolcuster was also reported for AgCu 16 nanocluster in the recent studies of Han et al [33] As shown in Figure S2, TGA reveals a weight loss of 42.96%, which is very close to the theoretical value (43.16%) for [Ag 45 Cu 17 S 12 (SC 4 H 9 ) 32 ](BPh 4 ) 4 . XPS measurements were carried out to reveal the element type and compared the binding energies of Ag in Ag 62À x Cu x and Ag 62 .…”
Section: Synthesis and Characterization Of Ag 62à X Cu Xsupporting
confidence: 83%
“…There were also no other fragment peaks detected under in-source energy-dependent mass spectra between 0 and 100 eV, further indicating the excellent stability of MoS-MBTZ. 49,50 As the voltage of the ion source was increased, the intensity of the fragment peaks attributed to the dimers gradually decreased and eventually disappeared as the weak interaction between the clusters in a dimer is overcome (Fig. 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the quantum connement effect, the discrete energy level of the NC offers unprecedented opportunities to nd optoelectronic applicability. 24,68,69 DFT calculations were employed to scrutinize the electronic structure of the Cu 18 NC. The projected density of states (PDOS) analysis reveals that the valence band region of this NC is predominantly occupied by Cu(d) states (Fig.…”
Section: Resultsmentioning
confidence: 99%